2017
DOI: 10.4055/cios.2017.9.4.497
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Graft in Irreparable Massive Rotator Cuff Tears: Autogenic Biceps Graft versus Allogenic Dermal Patch Graft

Abstract: BackgroundFew comparative studies have reported on the use of biologic grafts for irreparable massive rotator cuff tears. The purpose of this study was to assess the results of arthroscopic bridging graft in irreparable massive rotator cuff tears using an autogenic long head of biceps tendon (LHBT) or an allogenic dermal patch (ADP).MethodsWe retrospectively reviewed 24 patients treated using the LHBT (group I) and eight patients with complete rupture of the LHBT treated using an ADP (group II) since 2011. Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 28 publications
1
37
0
Order By: Relevance
“…Despite this, they too demonstrated improved functional scores in University of California, Los Angeles (UCLA) shoulder score. Previous studies that can provide a direct comparison to our data showed similar functional scores postoperatively: Modi et al7) showed a mean Constant score of 42; Rhee and Oh11) showed a comparable QuickDASH score of 20.9 ± 3.6 and also a comparable retear or failure rate seen on MRI of 75% in their “bridging” group at 1 year postoperatively. We think that the functional scores and patient-perceived improvement are due to the graft preventing proximal migration and abutment of the humeral head and are likely to be short-lived as the graft becomes thin, macerated, and tears away from the tendinous stump.…”
Section: Discussionsupporting
confidence: 80%
“…Despite this, they too demonstrated improved functional scores in University of California, Los Angeles (UCLA) shoulder score. Previous studies that can provide a direct comparison to our data showed similar functional scores postoperatively: Modi et al7) showed a mean Constant score of 42; Rhee and Oh11) showed a comparable QuickDASH score of 20.9 ± 3.6 and also a comparable retear or failure rate seen on MRI of 75% in their “bridging” group at 1 year postoperatively. We think that the functional scores and patient-perceived improvement are due to the graft preventing proximal migration and abutment of the humeral head and are likely to be short-lived as the graft becomes thin, macerated, and tears away from the tendinous stump.…”
Section: Discussionsupporting
confidence: 80%
“…Until now, many studies have reported on the procedures used for massive rotator cuff tear, e.g., debridement [1], biceps tenotomy [2,3], partial repair [4,5], patch graft [6][7][8], latissimus dorsi transfer [9,10] and reverse total shoulder arthropathy (RSA) [11,12]. However, it is not easy to obtain satisfactory results via any of the surgical methods and symptoms, such as dysfunction and pain, may persist after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the 1-year follow-up retear rate was 75% in them. 45) Some studies have suggested methods to overcome failure after massive RCT repair. Yoon et al 46) performed patch augmentation and bone marrow stimulation in 21 patients with massive RCTs and compared the results with those of conventional repair performed in 54 patients.…”
Section: Graft Augmentationmentioning
confidence: 99%
“…On the basis of conflicting outcomes documented in previous studies, the efficacy of allograft has yet to be elucidated in further research. Since differences in the composition of study population and the purpose of grafting (bridging or augmentation) affect the resultant healing rates, 45) it is of utmost importance to ensure proper patient selection. Compared to concomitant multiple channeling and augmentation, 46) the outcomes of platelet-rich plasma injection plus graft augmentation reported in recent studies have been less than satisfactory.…”
Section: Graft Augmentationmentioning
confidence: 99%